Legitymacja demokratyczna władzy sądowniczej w prawie hiszpańskim - Stępień-Załucka, Beata (PRAWO i WIĘŹ, 2025)
One of the main problems of the judiciary in recent years has been the issue of its legitimacy. The changes that have taken place in Poland, among other countries, have renewed the discussion on the system of judicial appointment, the possible participation of representatives of authorities other than the judiciary in the relevant procedures, or – consequently – the discussion on the status of judges appointed with the participation of the non-judicial community. One of the countries where judges do not, in principle, play a decisive role in judicial appointment procedures is Spain. The Spanish legal system emphasises the important links between the judiciary and the will of the nation, pointing to the need to provide judges with so-called democratic legitimacy. Therefore, the author looks at the Spanish system and tries to answer questions about the relevance of the concept of democratic legitimacy of the judiciary for the functioning of the Spanish legal system. The analysis is based on traditional scientific methods used in legal studies, which aim, among other things, to examine the consequences of transferring Spanish standards to the Polish context